Clofazimine broadly inhibits coronaviruses including SARS-CoV-2 - Yuan, Shuofeng; Yin, Xin; Meng, Xiangzhi; Chan, Jasper Fuk-Woo; Ye, Zi-Wei; Riva, Laura; Pache, Lars; Chan, Chris Chun-Yiu; Lai, Pok-Man; Chan, Chris Chung-Sing; Poon, Vincent Kwok-Man; Lee, Andrew Chak-Yiu; et al. (Nature (London), 2021)
The COVID-19 pandemic is the third outbreak this century of a zoonotic disease caused by a coronavirus, following the emergence of severe acute respiratory syndrome (SARS) in 2003 1 and Middle East respiratory syndrome (MERS) in 2012 2 . Treatment options for coronaviruses are limited. Here we show that clofazimine—an anti-leprosy drug with a favourable safety profile 3 —possesses inhibitory activity against several coronaviruses, and can antagonize the replication of SARS-CoV-2 and MERS-CoV in a range of in vitro systems. We found that this molecule, which has been approved by the US Food and Drug Administration, inhibits cell fusion mediated by the viral spike glycoprotein, as well as activity of the viral helicase. Prophylactic or therapeutic administration of clofazimine in a hamster model of SARS-CoV-2 pathogenesis led to reduced viral loads in the lung and viral shedding in faeces, and also alleviated the inflammation associated with viral infection. Combinations of clofazimine and remdesivir exhibited antiviral synergy in vitro and in vivo, and restricted viral shedding from the upper respiratory tract. Clofazimine, which is orally bioavailable and comparatively cheap to manufacture, is an attractive clinical candidate for the treatment of outpatients and—when combined with remdesivir—in therapy for hospitalized patients with COVID-19, particularly in contexts in which costs are an important factor or specialized medical facilities are limited. Our data provide evidence that clofazimine may have a role in the control of the current pandemic of COVID-19 and—possibly more importantly—in dealing with coronavirus diseases that may emerge in the future. The anti-leprosy drug clofazimine inhibits coronavirus replication in several cell models and shows potent antiviral activity against SARS-CoV-2 infection in a hamster model, particularly when used in combination with remdesivir.